Komisi Kebenaran dan Rekonsiliasi dalam Era Nontransisional: Implementasi di Korea Selatan dan Kanada - Anggarani Utami Dewi; Mustafa Fakhri (Badan Strategi Kebijakan Hukum, 2022)
This article aims to explain the practice of Truth and Reconciliation Commission (TRC) in non-transitional era. The TRC in non-transitional era was formed by democratic country or to reveal the truth of gross human rights violations that occurred decades ago. This research uses comparative method that compares the practice of TRC in South Korea (Commission on Clearing up Past Incidents for Truth and Reconciliation/TRCK) and Canada (Truth and Reconciliation Commission of Canada/TRCC). The results of the study indicate that the TRCK and TRCC were formed as an effort by the state to improve previous efforts in dealing with gross human rights violations; the number of staff members had a more significant impact on the success of the TRC than the number of commissioners; the norms governing the protection, prohibition, and sanctions for commissioners and staff, testifying witnesses, the persons named in the testimony and for individual and community; TRCK and TRCC gathered facts within two years; and the reconciliation process was carried out by the commission through the rehabilitation of reputations and holding memorial services. This article recommends that the practice of TRC in South Korea and Canada can be adopted in the preparation of policies for the establishment of TRCs in Indonesia.